Teaching Quebec Film. Reflections of an American Academic - Donohoe, Joseph (Cinémas, 1997)
After recounting the origins of his interest in Quebec cinema, the author discusses several of the films which he has utilized over the years in his undergraduate classes (Mon oncle Antoine, Pour la suite du monde and Sonatine) from the points of view both of what they mean to him, how he teaches them and how they have been received by his students. In conclusion, he presents an argument in favor of the "cultural transparency" of films destined for the world market.